The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.3390/insects13100954
|View full text |Cite
|
Sign up to set email alerts
|

Toxicity of Some Essential Oils Constituents against Oriental Fruit Fly, Bactrocera dorsalis (Hendel) (Diptera: Tephritidae)

Abstract: The massive use of synthetic pesticides to manage agricultural pests results in environmental pollution and health hazards. The secondary plant metabolites, which are majorly dominated by terpenoids, have the potential to be developed into novel alternatives to synthetic chemicals. Therefore, in our current investigation, six majorly dominated essential oil constituents were evaluated for their toxicity against adults and immature stages of oriental fruit flies, Bactrocera dorsalis, a worldwide fruit pest. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 70 publications
0
11
0
Order By: Relevance
“…Plant volatiles as an alternative to synthetic chemicals in pest management has been emphasized in several studies (Figure 3) (Ameye et al, 2018, 2015; Isman, 2020; Jaffar & Lu, 2022). For example, studies have shown that the plant volatiles, such as methyl salicylate, linalool, carvacrol, limonene and β‐caryophyllene, can enhance the effectiveness of IPM programs.…”
Section: Significant Role Of Plant Volatiles In Ipmmentioning
confidence: 99%
See 2 more Smart Citations
“…Plant volatiles as an alternative to synthetic chemicals in pest management has been emphasized in several studies (Figure 3) (Ameye et al, 2018, 2015; Isman, 2020; Jaffar & Lu, 2022). For example, studies have shown that the plant volatiles, such as methyl salicylate, linalool, carvacrol, limonene and β‐caryophyllene, can enhance the effectiveness of IPM programs.…”
Section: Significant Role Of Plant Volatiles In Ipmmentioning
confidence: 99%
“…In addition, numerous studies have investigated the role of plant volatiles in reducing pest population damage to crops. For instance, 2‐undecanone, limonene, α‐pinene, β‐pinene and trans‐β‐farnesene have shown potential in repelling pests from fruit and crops (Cui et al, 2012; Jaffar & Lu, 2022; Ntalli et al, 2016; Zapata & Smagghe, 2010). Furthermore, plant volatiles have been demonstrated to be highly effective in monitoring and detecting pest populations (Conboy et al, 2020).…”
Section: Significant Role Of Plant Volatiles In Ipmmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, D-limonene was present in salivary gland extracts of Ceratitis capitata [145] and D-limonene had an attractive effect on H. irritans irritans at concentrations below 0.1%, indicating that D-limonene has potential application in trapping these insects [144]. In addition, D-limonene not only inhibited the fecundity activity of Bactrocera dorsalis but also showed a significant toxic effect on adults and pupae and exhibited a dose-dependent killing effect on larvae [146]. However, Papanastasiou et al [147] found that D-limonene exhibited acute toxicity to the insect at high concentrations but promoted its survival and reproduction at low concentrations, probably due to the hormetic-like effect of D-limonene.…”
Section: Anthelmintic and Insecticidal Activitymentioning
confidence: 99%
“…These ndings highlight the potential of non-consumptive pest control strategies in reducing pest populations and impacting population dynamics.Several repellent chemicals have been assessed for their effectiveness against B. dorsalis, such as botanicals from Seriphidium brevifolium, Piper nigrum, Azadirachta indica, and quercetin, as well as various oils. These compounds have shown promising results in repelling B. dorsalis and reducing crop damage(Liu et al 2019;Jaleel et al 2020;Jaffar et al 2022). However, their e cacy in natural environments remains uncertain.…”
mentioning
confidence: 99%